2014
DOI: 10.3747/co.21.1662
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a “community of practice” methodology as a regional platform for large-scale collaboration in cancer surgery—the Ottawa approach

Abstract: not on the role of cops in large-scale collaborations across multiple disciplines 6,7 .The idea that a cop can be deliberately started and supported by an organization to facilitate multiprofessional collaboration is a new and emerging area of enquiry. It has also been increasingly used as a theoretical approach to analyze and compare large-scale health care collaborations 1,5,8 . Additionally, a number of recent research findings have suggested that features of cop might be beneficial in addressing the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…In some cases, preexisting and “slumbering” CoPs can be leveraged when intentionally developing CoPs by “manipulating emergence” of new CoPs (Kislov, Walshe, & Harvey, ) and relying on the preexisting network and social capital (Fung‐Kee‐Fung et al, ; Iaquinto, Ison, & Faggian, ). By making CoP participation voluntary, the employees are allowed to decide whether the CoP is relevant for their jobs (Fung‐Kee‐Fung, Boushey, & Morash, ; Hemmasi & Csanda, ; Scarso et al, ) and to choose if the CoP focus is of practical interest to them (Akkerman et al, ; Wolf, Späth, & Haefliger, ). In this way, the CoP should include only genuinely involved and interested employees, which favours its successful development (Wenger, ).…”
Section: Communities Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, preexisting and “slumbering” CoPs can be leveraged when intentionally developing CoPs by “manipulating emergence” of new CoPs (Kislov, Walshe, & Harvey, ) and relying on the preexisting network and social capital (Fung‐Kee‐Fung et al, ; Iaquinto, Ison, & Faggian, ). By making CoP participation voluntary, the employees are allowed to decide whether the CoP is relevant for their jobs (Fung‐Kee‐Fung, Boushey, & Morash, ; Hemmasi & Csanda, ; Scarso et al, ) and to choose if the CoP focus is of practical interest to them (Akkerman et al, ; Wolf, Späth, & Haefliger, ). In this way, the CoP should include only genuinely involved and interested employees, which favours its successful development (Wenger, ).…”
Section: Communities Of Practicementioning
confidence: 99%
“…CoP is a social phenomenon, hence physical interaction between CoP members is regarded as important for its success (Fung‐Kee‐Fung, Boushey, Watters, et al, ; Iaquinto et al, ; Orr, ; Wenger et al, ), whereas reduced face‐to‐face interaction is found to have negative effects on CoP performance (Schenkel & Teigland, ). A meeting between CoP participants must provide a risk‐free zone, which caters for participants' ability to ask questions without risk of sanction (Borzillo, ), enable in‐depth and undisturbed discussions (Orr, ), and facilitate a collaborative work effort (Fung‐Kee‐Fung, Boushey, & Morash, ). A designated meeting room for the CoP can fulfil this function.…”
Section: Communities Of Practicementioning
confidence: 99%
“…A cop, in this context, is a collective of multiple stakeholders outside of the hierarchy of their institution, considered equal, and sharing a common goal of learning and sharing in order to improve something, in this case, lung cancer care. Application is described in detail in our previous publications [21][22][23][24][25] . This has provided the regional foundation for the awareness and trusted relationships necessary to create positive perceptions of change, commitment, and ownership of large scale improvements.…”
Section: Practical Development Of a Learning Health System In Cancermentioning
confidence: 99%
“…Interestingly, the most successful quality improvement programs are those that engage physicians in development and implementation. One such effort is the Community of Practice effort in surgical oncology in Ontario Canada . This effort demonstrates the effectiveness of grass‐roots involvements of practicing surgeon in substantive quality improvement.…”
Section: Programs In Use Applying Breast Quality Measuresmentioning
confidence: 99%